Gross, histological and ultrastructural morphology of the aglomerular kidney in the lined seahorse Hippocampus erectus. Issue 3 (September 2015) - Fogelson, S. B.; Yanong, R. P. E.; Kane, A.; Teal, C. N.; Berzins, I. K.; Smith, S. A.; Brown, C.; Camus, A.
<x xml:space="preserve">Abstract</x> Histologic evaluation of the renal system in the lined seahorse Hippocampus erectus reveals a cranial kidney with low to moderate cellularity, composed of a central dorsal aorta, endothelial lined capillary sinusoids, haematopoietic tissue, fine fibrovascular stroma, ganglia and no nephrons. In comparison, the caudal kidney is moderately to highly cellular with numerous highly convoluted epithelial lined tubules separated by interlacing haematopoietic tissue, no glomeruli, fine fibrovascular stroma, numerous capillary sinusoids, corpuscles of Stannius and clusters of endocrine cells adjacent to large calibre vessels. Ultrastructural evaluation of the renal tubules reveals minimal variability of the tubule epithelium throughout the length of the nephron and the majority of tubules are characterized by epithelial cells with few apical microvilli, elaborate basal membrane infolding, rare electron dense granules and abundant supporting collagenous matrix.